An empirical analysis of premature deindustrialization in latecomer developing countries - Taguchi, Hiroyuki; Kosegawa, Ryo (The Economics and Finance Letters, 2023)
The purpose of this study is to investigate the phenomenon of premature deindustrialization among latecomer economies in developing countries across the globe. This study applies a fixed effect model based on panel data as a methodology. The main findings and conclusions of this study are as follows: First, the fixed effect model based on panel data, which was used as a baseline analysis for looking at the link between manufacturing and income using the latecomer index, found that developing economies that joined the global economy after 1990 were deindustrializing too quickly. Second, from a geographical perspective, the acceleration of premature deindustrialization was confirmed in Latin America and some areas of Africa. Third, the quantile regression, which was used to test how stable the results of the fixed effect model estimation were, found that developing economies were deindustrializing too soon. Finally, alternative estimations demonstrated that partaking in global value chains (GVC) facilitated industrialization, whereas natural resource abundance prevented it. In terms of practical implications, GVC participation can be a good way for latecomer in developing economies to avoid premature deindustrialization. Resource-rich economies could keep the Dutch disease effect from speeding up premature deindustrialization by putting their resource revenues to productive uses, like building infrastructure.